DEVELOPMENT OF STUDENT WORKSHEET BASED ON PROBLEM BASED LEARNING APPROACH TO INCREASE 7TH GRADE student's CREATIVE THINKING SKILLS - Siska Febriani; Joko Sudomo; Wita Setianingsih (Universitas Negeri Yogyakarta, 2017)
The research aims to (1) produce a student worksheet based on problem based learning that has the potency to improve the 7th grade student's creative thinking skill based on assessment of expert lecturers and science teachers on the content business feasibility component, language and image component, component, and presentation graphics component, (2) know the student response toward the student worksheet based on problem based learning to improve the 7th grade student's creative thinking skills, (3) know the improvement the 7th grade student's creative thinking skills after using the student worksheet based on problem based learning. The design of this research was Research and Development model with 4 d development model which includes define, design, develop, and disseminate. The data analysis technique of appropriateness of the student worksheet and students responses to the student worksheet is quantitative score conversion to qualitative value with five categories, the data analysis technique of the implementation of the problem based learning model and student's creative thinking skill based on observation is a percentage calculation, while the data analysis technique of creative thinking skills pre test and post test is normalized gain score (N-gain score). Based on the results of the research, it can be concluded that (1) a student worksheet based on Problem Based Learning has the potency to improve the 7th grade student's creative thinking skill based on assessment of expert lecturers and science teachers on the content business feasibility component, language and image component, component, and presentation graphics component get score 105.75 of a maximum score of 120 with a value of